Aplikasi TASING dan Video Conference dalam Peningkatan Pengetahuan dan Sikap Remaja Perempuan dalam Pencegahan Stunting - Sarita, Rezeki Oktari; Mardiani, Mardiani; Wijaya, Andra Saferi (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Muhammadiyah Makassar, 2024)
Stunting is a condition where a person's height is less than normal based on age and gender. Stunting can impact motor and verbal development, increase degenerative diseases, morbidity and mortality. This research is quantitative research, this type of research uses the pre-experimental design method, with one group pre-test and post-test research. The sampling technique in this research is purposive sampling. The sample taken in this research was the whole or also called total sampling with a total of 50 female students. Data analysis in this study used the Sapiro Wilk test. It is hoped that this research can increase knowledge and provide references and information for researchers who wish to conduct further research related to preventing stunting in adolescent girls.